KADAR ELEKTROLIT DALAM DARAH PADA TENAGA KERJA YANG TERPAPAR PANAS (Studi Kasus Pada Bagian Welding Di PT. DOK Dan Perkapalan Surabaya (Persero) Tahun 2016) - Fitria Alfiatus Solikhah; Hadi Suryono; Rusmiati . (GEMA LINGKUNGAN KESEHATAN, 2017)
ABSTRACTElectrolytes are salts that ionized or broken down into positive and negative ions in the body. Thefunction of liquid electrolytes in the body is to maintain the structure of the cells through osmotic effects and asan integral part of the process of cellular metabolism.This research used descriptive method by observation, interviews and measurements to determineelectrolytes blood level on the working labors. Samplings were acquired by using random sampling of 18 samplesfrom 27 populations.From the research, the majority of respondents age 40 years (88.9%), length of working 5 years(88.9%), drinking water intake 2 liters (61.1%), electrolyte levels were Imbalance (72.2 %), working climatewas 31C.The conclusion of this study that the characteristics of employment and levels of electrolyte did notaffect the health of the working labors. Therefore, the company was suggested to add natural or artificialventilation thus the working climate in the workshop rooms would be comfortable.Keywords : electrolytes, hot climate, welding, personal protective equipment